Consumers’ online decision-making process toward sustainable apparel: an exploratory study using eye-tracking technology. - Islam, Md Mayedul (Kansas State University, 2019)
Marketing of sustainable apparel could have several inherent barriers including the higher product price, limited choices, aesthetic disadvantages, and complexity of information. Individuals working in the field of sustainable apparel need to know the important attributes such as price and consumer review provided with a product that consumers focus on during their decision-making process to encourage consumption of sustainable apparel. Recently, online apparel sales grew at a higher rate than the overall apparel sales did. However, no existing research has studied how online presentation of the sustainability attributes of an apparel product influences consumers’ online purchasing behaviors. Therefore, this study investigated 1) how sustainability attributes of apparel products presented on a website influence the purchase decision of a participant, and 2) how a consumers’ level of concern on the environmental impact of the apparel industry influence his/her purchase decision. Additionally, this study explored the potential usage of eye-tracking technology (ET) as a tool for investigating consumers' online purchasing decision-making process, particularly for sustainable apparel. The study consists of two phases. The first phase was a survey, and the second phase was an eye-tracking study plus an exit survey. An online survey was administered to more than three hundred fifty 18-65 years old participants to collect demographic information, information of purchasing behavior, and level of concern on the environmental impact of the apparel industry. Based on the score of concern, the respondents were categorized into a lower concern group (lower 33%) and a higher concern group (upper 33%). Later, eligible participants in each group were invited to participate in the second phase. Participants were provided with screenshots of apparel from the website of two selected brands including a more sustainable apparel brand (Patagonia) and a less sustainable apparel brand (Adidas). They were instructed to wear a pair of eye-tracking glasses during the evaluation process. Immediately after completing the eye-tracking recording, participants completed an exit survey where they were asked to respond to the questions about the eye-tracking experience and indicate which out of the two brands they would most likely to purchase. Data were analyzed using independent samples T-test and Mann-Whitney’ Wilcoxon test. By examining the gaze behavior and self-reported data of the participants, this study found that sustainability attributes may influence the purchase decision when consumers have a higher concern on the environmental impact of the apparel industry and place adequate attention to these attributes. In addition, findings indicate that consumers’ existing concern for apparel industry impact has no significant effect on consumers' online decision-making for the purchase of sustainable apparel. This study offers insights into how consumers’ attention works in the decision-making process for online marketing of sustainable apparel. Limitations of the study are discussed.
Keywords: Sustainable apparel; Eye-tracking technologyConsumers’ online decision-making process